The role of thyroid hormones in assessing the survival of intensive care unit patients - Bartolović, Daniela; Jovičić, Snežana; Terzić, Branka (Vojnosanitetski pregled, 2024)
Background/Aim. Patients in intensive care units (ICUs) often exhibit disturbances in the concentration of thyroid hormones (THs), even if they had no previous thyroid disorders. The aim of the study was to determine whether there is a correlation between THs and the survival rate in the ICU and whether these hormones have predictive capability for mortality rate assessment. Methods. The study included 41 patients (23 women and 18 men) divided into two groups: survivors (70.7%) and non-survivors (29.3%). In peripheral blood samples taken within the first 24 hrs after ICU admission, TH levels were measured: triiodothyronine (T3), thyroxine (T4), free T3 (FT3), free T4 (FT4), and thyroid stimulating hormone (TSH), as well as procalcitonin (PCT). The Sequential Organ Failure Assessment Score (SOFAS) was calculated for each patient. Results. A statistically significant difference between the study groups (survivor vs. non-survivor patients, p < 0.05) was found for PCT, SOFAS, T3, T4, and FT4. The area under the receiver operating characteristic (ROC) curve (AUC) – (AUROC) for the SOFAS was 0.991 [95% confidence interval (CI): 0.898–1.000, p < 0.001], for T3 was 0.727 (95% CI: 0.566–0.854, p = 0.0097), for T4 was 0.793 (95% CI: 0.638–0.903, p = 0.0008), for FT3 was 0.707 (95% CI: 0.544–0.8389, p = 0.0299), and for FT4 was 0.795 (95% CI: 0.640–0.904, p = 0.0005). Compared to other parameters, T3 had higher sensitivity (91.67%), FT4 had higher specificity (93.10%), while SOFAS had both the highest sensitivity (91.67%) and specificity (96.55%) in relation to all other tested parameters. Multiple linear regression analysis showed that FT4 and T4 were significant predictors of survival time (β = -0.362, p = 0.012 and β = -0.356, p = 0.014, respectively). Conclusion. Among all examined THs, only FT4 and T4 showed strong predictive potential for assessing mortality in ICU patients. This study has highlighted the significance of assessing THs levels in critically ill patients. This is crucial because it opens the possibility of implementing specific therapies to rectify issues stemming from hormonal deficiencies.